Electronic library services in Hungary and in the USA (Libellarium: journal for research in the field of information and related sciences, 2017)
The primary purpose of the research was a comparative analysis of computerized integrated library systems (WebOPAC) based on and/or providing Web 2.0 services, by reviewing several important library systems of Hungary and the USA. The research was conducted in all of the 19 Hungarian county libraries and the libraries of 67 higher education institutions in Hungary. Besides, the integrated library systems of 39 university libraries in the USA were also analyzed. Both inductive and quantitative methods were applied.In this study, the selected Hungarian and American university libraries were studied from the point of view of Web 2.0 services. The main features of Web 2.0 services provided by those libraries were compared. In addition, content elements and statistical data were analyzed, major differences were referred to, and additional effective internet services were suggested to be introduced in the future.
Keywords: University; libraries; Web 2.0; Startup; statistics